Law, Psychology & Morality - Bilz, Kenworthey (2008)
In a democratic society, law is an important means to express, manipulate, and enforce moral codes. Demonstrating empirically that law can achieve moral goals is difficult. Nevertheless, public interest groups spend considerable energy and resources to change the law with the goal of changing not only morally-laden behaviors, but also morally-laden cognitions and emotions. Additionally, even when there is little reason to believe that a change in law will lead to changes in behavior or attitudes, groups see the law as a form of moral capital that they wish to own, to make a statement about society. Examples include gay sodomy laws, abortion laws, and Prohibition. In this Chapter, we explore the possible mechanisms by which law can influence attitudes and behavior. To this end, we consider informational and group influence of law on attitudes, as well as the effects of salience, coordination, and social meaning on behavior, and the behavioral backlash that can result from a mismatch between law and community attitudes. Finally, we describe two lines of psychological research—symbolic politics and group identity— that can help explain how people use the law, or the legal system, to effect expressive goals